Perbedaan Prinsip Profesi Guru BK dan Rekan Sejawat di SMP Negeri 1 Tanjung Balai - Tri Rizky Ramadhani; Riwayati Octaria Pakpahan; Dio Alpian Sitio; Sekar Ayu Pratiwi; Rizky Ananda Syafitri (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to identify and analyze ethical code violations among Guidance and Counseling (GC) teachers. The research employs a qualitative approach with a case study method, involving in-depth interviews with a GC teacher at SMP Negeri 1 Tanjung Balai. The results reveal several challenges in implementing the code of ethics, such as colleagues' lack of understanding about the role of GC teachers, difficulties in building cooperation with homeroom teachers and other subject teachers, and challenges in communicating with parents from diverse backgrounds. The study also highlights the importance of maintaining student information confidentiality and upholding professional boundaries in relationships with colleagues. These findings emphasize the need for more intensive professional ethics training for GC teachers and increased awareness of their crucial role within the broader school community.